Executive functions predict weight loss in a medically supervised weight loss programme. (28th September 2016) - Galioto, R.; Bond, D.; Gunstad, J.; Pera, V.; Rathier, L.; Tremont, G.
Summary: Background: Deficits in executive functions are related to poorer weight loss after bariatric surgery; however, less is known about the role that these deficits may play during participation in nonsurgical weight loss programmes. This study examined associations between objectively measured executive functions and weight loss during participation in a medically supervised weight loss programme. Methods: Twenty‐three adult patients (age 50.4 ± 15.1, BMI 44.2 ± 8.8, 68% female, 92% White) enrolled in a medically supervised weight loss programme, involving prescription of a very low calorie diet and strategies to change eating and activity behaviours, underwent comprehensive computerized testing of executive functions at baseline. Weight was obtained at baseline and 8 weeks. Demographic and clinical information were obtained through medical chart review. Results: Participants lost an average of 9.8 ± 3.4% of their initial body weight at 8 weeks. Fewer correct responses on a set‐shifting task and faster reaction time on a response inhibition task were associated with lower weight loss percentage at 8 weeks after adjusting for age, education and depressive symptoms. There were no associations between performance on tests of working memory or planning and weight loss. Conclusions: This study shows that worse performance on a set‐shifting task (indicative of poorer cognitive flexibility) and faster reaction times on a response inhibition test (indicative of higher impulsivity) are associated with lower weight loss among participants in a medically supervised weight loss programme. Pre‐treatment assessment of executive functions may be useful in identifying individuals who may be at risk for suboptimal treatment outcomes. Future research is needed to replicate these findings in larger samples and identify underlying mechanisms.